Passive Techniques and Sustainable Urban Development: The Use of Traditional Building Solutions for Climatic Design of Sustainable Urban Texture in Desert Regions - Madadi-Kandjani, Elham; Hofbauer, Christian Kersten; Meuwissen, Jean Marie Corneille (Journal of Environmental Accounting and Management, 2026)
Climate and geographical conditions have had a significant impact on the arrangement of architectural elements and physical features of building in hot and dry areas in the past. Without all our modern “science” and “economy”, the builders of the time achieved results based on traditional wisdom and knowledge of the different local conditions, which should guide us in our endeavors to build for a traditional life, to humanize the living space. The aim of this paper is to figure out the criteria of ancient urban and rural settlements in deserts and to introduce some traditional and sustainable features of arid areas in old buildings in hot and arid regions, which show us designing in harmony with nature, and how our ancestors overcame difficult conditions in deserts. In our industrial age, the natural wishes and needs of the inhabitants have been sacrificed for the sake of business. But to take these characteristics into consideration could help us to mitigate human tensions and to solve many problems of today’s life.